The Effect of Human Resources Competence and Internal Control System on the Quality of Financial Statements with Organizational Commitment as a Moderating Variable at Three Public Hospitals in Pangkalan Kerinci - Riau - Perlaban karo-karo; Irfan Irfan; Zulia Hanum (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of human resource competence and control systems on the quality of financial reports with organizational commitment as a moderating variable. The research method used is quantitative research. The primary data used is data from questionnaires that are measured using a Likert scale. Population in this study were 3 hospitals in Pangkalan Kerinci, Pelalawan Regency, Riau. Determination of the sample was carried out using a purposive sampling method, in order to obtain a sample of 30 respondents. The research data were collected using a questionnaire which was then processed by the F test, t test and MRA test with the help of SPSS (Statistical Program for Social Science) version 22. The results of the study stated that (1) the competence of human resources had on the quality of financial reports, (2) the control system internal has on the quality of financial reports, (3) organizational commitment is unable to moderate the effect of human resource competence on the quality of financial reports, and (4) organizational commitment is unable to moderate the effect of the internal control system on the quality of financial reports.